Investigation of Life Long Learning Tendencies of Undergraduate Students in Turkey - Sadık Yüksel Sıvacı; Mustafa Kılınç; Mustafa Köroğlu; Enes Demirel (Journal of Educational Issues, 2024)
Investigation the lifelong learning tendencies of undergraduate students, who are legally adults, have gained their own learning responsibilities and are expected to strive for continuous self-improvement, is extremely important in terms of adapting to modern life and reaching the most accurate and up-to-date information against the ever-changing and developing information volume. In this context, the aim of the research is to determine the lifelong learning tendency levels of undergraduate students and to examine their lifelong tendencies in terms of various variables. The research is a study in survey model. The study group of the research consists of 2713 undergraduate students studying at Burdur Mehmet Akif Ersoy University in the 2020-2021 academic year. The “Lifelong Learning Tendency Scale” developed by Diker-Coşkun (2009) was used as the data collection tool. According to the results of the research, it was found that undergraduate students had a high level of lifelong learning tendency, and their lifelong learning tendency levels showed significant difference according to the variables of gender, age, grade level, cumulative grade point average, socio-economic level of the family, department and university satisfaction. It was also found that there was no statistically significant difference according to the place of residence variable. According to the findings, suggestions were made for increasing the lifelong learning tendencies of undergraduate students and for new studies.